CORRUPTION AS A THREAT OF ECONOMIC SECURITY OF UKRAINE - Шведова, Ганна Леонідівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: in the article the contemporary challenges and threats to Ukraine’s economic security were considered. The corruption risks that can adversely influence on the economic security are identified. The possible ways of it’s eliminating are determined. Methods: a set of general and special methods of scientific knowledge – the terminology, logical-semantic, functional, system-structural, logical and normative. Results: it is revealed that the current criminogenic situation in Ukraine is a qualitatively new phenomenon, that threatens to the national, including economic security. Corruption risks and threats are form the basis for the spread of economic organized criminality, the growth of the «shadow economics». Such problems need more advanced counteraction technologies. Among the priority measures to overcome corruption are the active de-shadowing of the economy, which involves: the identification and elimination of the economic basis of organized criminality in the most profitable strategic areas (budget, tax, foreign-economic, credit and bank); the establishing an effective mechanism for the return of illegally obtained (shrouded) funds (assets); upbringing the proper level of social, including the legal culture of all participants in economic relations. Discussion: the ways to limit corruption risks and threats for the effective functioning of objects of critical infrastructure and for the ensuring economic security of the state as a whole.